Customers preference on car among staffs in UiTM, Kota Kinabalu, Sabah / Evifyonne Masakit ... [et al.] - Masakit, Evifyonne; Hairudin, Fathiyah; Musa, Fazilah; Midi, Hervina; Saimon, Shila Amelia (2014)
In this fast moving era, transportation becomes one of the important necessity product. Due to the important and frequent use of the transportation, people need to buy their own car to assist them travel to their workplace, school and everywhere. However, there are many types of car brands available in the market that makes it difficult for consumers to make a choice. A good car brands is not a guarantee that the car will meet the consumers' expectation. Usually people will evaluate car based on their preference, thus the manufacture must identify consumers preference towards car to satisfy theit needs. Therefore, this study is conducted to find the car attribute that consumers more prefer when purchasing a car. As a result, the findings of this study will identify the consumer preferences on car during the purchasing process. In this study, we used sets of questionnaires to get the information from the respondents. Sets of questionnaires had been designed under the guidance of our lecturer and had gone through a few drafting stages before they were administered to the respondents. The questionnaires contained 29 items that helped elicit information about the respondent's background and responses pertinent to the study focus. The data collected were then analyzed by using SPSS. The frequency and percentage were calculated for each item After having much discussion with our lecturer on the chosen topic, we started to organize a brief observation after class to gain understanding on customers' preference on car. At the same time, we also keep searching literature review about the customer car preferences. This research was carried out since March. With the permission from our supervisor, we then approached the staffs in various departments and persuade them to participate in our study. We also did some readings on this matter by searching through the Internet. We managed to read up some newspaper articles and a summary of some research papers to get some common reasons for customers' preferences toward car. From the information gathered, we then built a set of questionnaires. The items in the questionnaires had been checked by our supervisor and had gone through moderation where necessary.